Exploring the Role of Artificial Intelligence in Enhancing Lean Manufacturing and Six Sigma for Smart Factories - Charles Onyeka Nwamekwe; Raphael Olumese Edokpia; Eboigbe Christopher Igbinosa (International Journal of Industrial Engineering, Technology & Operations Management, 2025)
The integration of Artificial Intelligence (AI) into Lean Manufacturing and Six Sigma methodologies marks a transformative advancement in smart factory operations. This research explores the pivotal role of AI in enhancing efficiency, quality, and sustainability across manufacturing processes. Case studies demonstrate how AI technologies, such as predictive maintenance and real-time monitoring, have significantly reduced downtime, optimized resource utilization, and improved product quality. AI-driven analytics and machine learning models further enable proactive decision-making, aligning Lean's waste-reduction principles and Six Sigma's quality-improvement goals. However, challenges such as high implementation costs, data privacy concerns, and workforce skill gaps impede widespread adoption. This paper discusses these barriers, proposes strategies to overcome them, and highlights opportunities to integrate AI into continuous improvement frameworks. Future research directions include developing scalable AI-driven methodologies, addressing ethical considerations, and exploring the role of AI in advancing sustainable manufacturing practices. The findings underscore AI's transformative potential to redefine Lean Six Sigma paradigms, driving innovation and operational excellence in the era of Industry 4.0.